IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT TO IMPROVE THE PERFORMANCE OF OFFICIALS AT BATA-BATA ENGLISH CENTER (BBEC) PAMEKASAN: TOTAL QUALITY MANAGEMENT TO IMPROVE THE PERFORMANCE OF OFFICIALS AT BATA-BATA ENGLISH CENTER (BBEC) PAMEKASAN - Hafidurrahman, Moh; Ach. Shobri; Umarul Faruk (Pendidikan Agama Islam, 2024)
ABSTRACT Total quality management is a management system that prioritizes quality as a strategy to attract customers, where customers here refer to the community and students. Mukolwe et al. emphasized that the implementation of total quality management in schools aims to produce better organizational performance. The reason for the need for TQM is very simple: the best way to remain competitive in global competition is to deliver the best quality through excellent service in a company. The performance of employees needs to be evaluated with the aim of providing a good opportunity for staff to plan their career paths based on their strengths and weaknesses, allowing the company to determine salaries, give promotions, and assess employee behavior. Performance is often interpreted as work output or achievement, although in reality, performance has a broader meaning because it not only refers to the outcome of work but also includes the process involved. Employee performance is defined as the ability of staff to carry out a specific skill. Employee performance is essential because it reveals how far the staff's ability goes in carrying out the tasks assigned to them. In this research, the researcher uses a quantitative research approach, meaning that the data analysis uses statistical analysis Keywords: Total Quality management, employee, performance. Kata Kunci: total Quality manajemen, kinerja, officials